ANALISIS MATERI POKOK ILMU PENGETAHUAN ALAM MI/SD - Mu'minatul Habibah (Jurnal Elementary : Kajian Teori dan Hasil Penelitian Pendidikan Sekolah Dasar, 2020)
Abstract. The science is one of the subjects often considered difficult by among learners, starting the ranks of primary education to high school. In reality the process of learning often performed is that students are charged with memorizing information without understanding the information obtained to connect it to the situations that occur in everyday life. The science aims to arouse human interest in order to be willing to increase intelligence and understanding of the nature at its disposal and train a learner can think critically and objectively. True knowledge means knowledge which is justified by denying the truth of a science, which is rational and objective.This article contains about the analysis of the staple matter of natural sciences MI/SD based on substance, space of inflammation, characteristics of the relevance of KD/Indicator/Goal/Material relating to the scientific structure, learner characteristics, HOTS, 4C, Science Literacy, digital Literacy, as well as Character Education. The study used a qualitative type approach with the method of library studies, as the study was conducted using a series of gatherings, processing and analyzing data drawn from written literatures